2009
DOI: 10.1016/j.jhealeco.2009.06.010
|View full text |Cite
|
Sign up to set email alerts
|

When are person tradeoffs valid?

Abstract: The person tradeoff (PTO) is commonly used in health economic applications. However, to date it has no theoretical basis. The purpose of this paper is to provide this basis from a set of assumptions that together justify the most common applications of the PTO method. Our analysis identifies the central assumptions in PTO measurements. We test these assumptions in an experiment, but find only limited support for the validity of the PTO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…However, several issues still remain as follows: the appropriateness of the health state or disease classification and valuation method, selection of survey participants to elicit preferences, validation of disability weights, and cross-cultural variability of disability weights (1112131415). In particular, the problem of using PTO or PHE was questioned in terms of the lack of theoretical basis (1617). …”
Section: Introductionmentioning
confidence: 99%
“…However, several issues still remain as follows: the appropriateness of the health state or disease classification and valuation method, selection of survey participants to elicit preferences, validation of disability weights, and cross-cultural variability of disability weights (1112131415). In particular, the problem of using PTO or PHE was questioned in terms of the lack of theoretical basis (1617). …”
Section: Introductionmentioning
confidence: 99%
“…The authorities have allocated large amounts of resources to increase the health infrastructure and the implementation of policies for prevention and care to achieve full health coverage for the entire population . The main goal objective of these policies is to improve the health of the population, which is equivalent, in measurable results, to an increase in life expectancy and quality of life …”
Section: Introductionmentioning
confidence: 99%
“…12 We have shown that a framework in which information on individual preferences over health is not available (either for practical or ethical reasons) still allows to make sound decisions over the evaluation of population health. 13 Somewhat related, even though we assume (as customary) that individual health is determined by two dimensions (quality and quantity) we do not presume that individuals evaluate them in a specific given way. In other words, as opposed to earlier axiomatic contributions on the evaluation of health profiles, we do not assume that the health of an individual is summarized by a number (to be interpreted as the number of QALYs, life years, or "health utility" experienced by a person), but by a duplet referring to the two dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…13 An alternative, albeit related, framework has been recently proposed by Fleurbaey and Shokkaert (2009), who include a concern for respecting individual preferences by means of a Pareto principle. Such Pareto principle implies that society is indifferent between a status quo and an hypothetical situation in which "healthy equivalent consumptions" are considered.…”
Section: Discussionmentioning
confidence: 99%